Determinants of Earnings and Gender Earnings Gaps among Highly Educated Workers within Major Cities in Asian Countries*. Issue 2 (7th July 2021) - Takeuchi, Mamiko
Abstract : The present paper analyzes determinants of earnings and the gender earnings gap among highly educated younger workers from nine major cities in Asian countries. We identify skill premiums for both men and women in each city, such as holding a postgraduate degree or degrees in specific fields and experience working or studying abroad. These results show that competition for earnings among highly educated younger workers has been increasing in these cities. Furthermore, the results reveal that, despite being quite narrow, significant gender gaps do exist; the means of log female earnings in each city range between 95.6 and 97.9 percent of those of men. Individuals having natural science degrees or managerial positions possibly affects these small gender gaps in some cities.